2018
DOI: 10.18488/journal.aefr.2018.82.294.307
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Factors Affecting the Timeliness of Financial Reports: The Experiments on Listed Companies in Vietnam

Abstract: Article History JEL Classification:M40, M419. This paper studies the factors affecting the timeliness of financial reports (FR) of enterprises in Vietnam. This research uses panel data with 1070 observations, at 214 companies listed on Vietnam's stock market in the period 2012 -2016. Retrieved results using the GLS method shows that there are 04 independent variables, including consolidated financial reports (CON), the audit firm (AUDIT), profitability (ROA) and the size of the business (SIZE) with relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 12 publications
2
20
0
6
Order By: Relevance
“…To maintain a good reputation in the community, large companies tend to be more timely in submitting financial reports. The research's results of Ha et al (2018), Kusumawardani & Priyadi (2018), and Hastutik (2015), explains that company size affects the timeliness of submitting financial statements. The larger the size of the company, the more resources it has.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To maintain a good reputation in the community, large companies tend to be more timely in submitting financial reports. The research's results of Ha et al (2018), Kusumawardani & Priyadi (2018), and Hastutik (2015), explains that company size affects the timeliness of submitting financial statements. The larger the size of the company, the more resources it has.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the factors that influence the timeliness of financial statement submission have been carried out. Many researchers examine the effect between timeliness of financial statements and accounting information, for example, Bagnoli et al (2002), Graham et al (2005), Sengupta (2004), Ha et al (2018), Raihani et al (2019). Many factors allow managers to provide annual and timely reports to reduce the cost of late reporting, for example, company size, current ratio, financial leverage, and profitability (G Hamidi & Rasouli, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors affect the timeliness of delivering financial statements including profitability, liquidity, company size, and the reputation of accounting firms. The first factor is that profitability is the company's ability to generate profits in the future, the profitability of a company is important information for investors as a consideration to investing the funds [2]- [5].The research that conducted by [6]- [8]revealed that profitability has a positive and insignificant effect on the timeliness of financial statements submission. Meanwhile, the research conducted by [9] and [10]states that profitability has a significant positive effect on the timeliness of financial statements submission.…”
Section: Introductionmentioning
confidence: 99%